The CEOS Recovery Observatory Pilot - S. Hosford; C. Proy; A. Giros; A. Eddy; I. Petiteville; C. Ishida; F. Gaetani; S. Frye; S. Zoffoli; J. Danzeglocke (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2015)
Over the course of the last decade, large populations living in vulnerable areas have led to record damages and substantial loss of life in mega-disasters ranging from the deadly Indian Ocean tsunami of 2004 and Haiti earthquake of 2010; the catastrophic flood damages of Hurricane Katrina in 2005 and the Tohoku tsunami of 2011, and the astonishing extent of the environmental impact of the Deepwater Horizon explosion in 2009. These major catastrophes have widespread and long-lasting impacts with subsequent recovery and reconstruction costing billions of euros and lasting years. While satellite imagery is used on an ad hoc basis after many disasters to support damage assessment, there is currently no standard practice or system to coordinate acquisition of data and facilitate access for early recovery planning and recovery tracking and monitoring. CEOS led the creation of a Recovery Observatory Oversight Team, which brings together major recovery stakeholders such as the UNDP and the World Bank/Global Facility for Disaster Reduction and Recovery, value-adding providers and leading space agencies. The principal aims of the Observatory are to: 1. Demonstrate the utility of a wide range of earth observation data to facilitate the recovery and reconstruction phase following a major catastrophic event; 2. Provide a concrete case to focus efforts in identifying and resolving technical and organizational obstacles to facilitating the visibility and access to a relevant set of EO data; and 3. Develop dialogue and establish institutional relationships with the Recovery phase user community to best target data and information requirements; The paper presented here will describe the work conducted in preparing for the triggering of a Recovery Observatory including support to rapid assessments and Post Disaster Needs Assessments by the EO community.